Experimental investigation of mechanical behaviors of EPS foamed concrete-filled pultruded GFRP sandwich panels - Sensen Li (Elsevier, 2021)
Pultruded sandwich panels (PSPs) usually possess lightweight but high load-carrying ability. One of the shortcoming is the low transverse shear resistance. To overcome this deficiency, Expanded Polystyrene (EPS) foamed concrete was designed, fabricated and filled into the web-core of the PSP. Flatwise compression experiments were performed to reveal the mechanical behaviors of the EPS foamed concrete varying with the density. Flexural experiments were conducted to reveal the flexural performances of the foam-filled PSPs, as well as the failure patterns. The bending rigidity of the PSPs is increased from 0.28 kN/mm from unfilled to 9.5 kN/mm after filling, and the bending rigidity of the PSPs is increased by 46.1 times. The load capacity of the PSPs is also profoundly improved from 3.02 kN to 23.63 kN. The failure pattern of the foam-filled PSP transforms from core shear failure, local indentation to mono-cell skin fracture when increasing the foam density.